A Review: Quorum Sensing Phenomenon: Regulation of biofilm in Pseudomonas aurogenosa - Rawa Abdul Redha Aziz; SuraAlaa Saud; Elaf Sameer Mohameed (Indian Journal of Forensic Medicine & Toxicology, 2021)
It is been mentioned that Pseudomonas aeruginosa, a ubiquitous, gram negative, can infect patients withCystic fibrosis. Treatment of infections can often be difficult due to its ability to produce biofilm. It has beenrevealed that biofilms are enclosing architecture that would consist of planktonic cells to survive in harshenvironments. Biofilm is usually comprised of Pel, Psl, and Alginate, and many others to make a scaffoldthat bacteria can attach and start making microcolonies. The formation of the biofilm and Alginate layer isshown to be controlled by intricate cell-to-cell communication known as quorum sensing (QS). Finally, inthis report, we have taken the basic principles of what is P.aerogenosa, and how it is related to the cysticfibrosis disease. Also, we have illustrated the formation of biofilms and the regulation of biofilms to thequorum sensing LasR/LasI and RhlR/RhlI systems.